Communication Skills of Students in the Application of Deep Learning at SD Muhammadiyah 1 Bangkalan - Hilda Yuliatina; Lilik Binti Mirnawati; Fajar Setiawan (Literasi Nusantara, 2026)
This study aims to describe the implementation of the Deep Learning approach and explore the communication skills of fourth-grade students at Muhammadiyah 1 Elementary School, Bangkalan, due to low participation and low quality of student idea delivery. Using a descriptive qualitative approach, data were collected through observation, semi-structured interviews, and documentation. Data were then analyzed using the Miles, Huberman, and Saldana model (data reduction, data presentation, and conclusion drawing). The results indicate that Deep Learning through authentic projects demonstrated changes in students' verbal participation patterns through collaborative tasks and improved the coherence of ideas due to the demands of critical thinking. This implementation fostered communication skills by facilitating the functional need to speak in small groups, which is an effective countermeasure to passivity in the classroom. However, its implementation still faced limitations due to the limited time allocated for in-depth dialogic discussions and teacher feedback that focused more on content than on the communication process. This study concludes that Deep Learning is a rich context, but it needs to be supported by a more active teacher role in providing explicit instruction and facilitating dialogue to optimize students' communication potential holistically.